2015
DOI: 10.4103/0189-6725.150977
|View full text |Cite
|
Sign up to set email alerts
|

Hypospadias repair and outcome in Abuja, Nigeria: A 5-year single-centre experience

Abstract: Background:To determine the outcome of hypospadias repair in children.Patients and Methods:This was a retrospective study of all patients with hypospadias managed at the University of Abuja Teaching Hospital, Abuja, Nigeria from January 2009 to December 2013.Results:Twenty-four cases of hypospadias had corrective surgery during the 5-year period under review. Seventy-five percent of the patients (n = 18) were seen after the 1st year of life. There were two peaks of ages at corrective repair; 45.8% between age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Apeadu-Mensah et al in 2007 found penile hypospadias as commonest (61%), [9]. and Osereman et al in 2015 found distal hypospadias as the commonest (58.4%) [10]. The GAP procedure can be used for both glanular hypospadias and coronal hypospadias.…”
Section: Discussionmentioning
confidence: 99%
“…Apeadu-Mensah et al in 2007 found penile hypospadias as commonest (61%), [9]. and Osereman et al in 2015 found distal hypospadias as the commonest (58.4%) [10]. The GAP procedure can be used for both glanular hypospadias and coronal hypospadias.…”
Section: Discussionmentioning
confidence: 99%
“…Its location varies along the ventral portion of the penis or in the perineum. The incidence of hypospadias is about 3.8 out of 1000 male live births [1], [2], [3], [4], [5]. Glanular hypospadias is the most common type of hypospadias reported.…”
Section: Introductionmentioning
confidence: 99%
“…Hypospadias is the abnormal location of the urethra on the ventral surface of the penis and in severe cases opens onto the scrotum or perineum 1 . It is often associated with incomplete development of the foreskin and abnormal penile curvature 2,3 . It is a common congenital malformation and the prevalence is reported to be increasing, although it has a large geographical variation ranging from 2 to 43 cases per 10,000 live births 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…It is a common congenital malformation and the prevalence is reported to be increasing, although it has a large geographical variation ranging from 2 to 43 cases per 10,000 live births 4,5 . The incidence is reported to be one in every 300 male live births 2 . The problem usually develops sporadically and without an obvious underlying cause 1 .…”
Section: Introductionmentioning
confidence: 99%